New Insights into Binding Interfaces of Coagulation Factors V and VIII and their Homologues - Lessons from High Resolution Crystal Structures - Fuentes-Prior, P.; Fujikawa, K.; Pratt, K.P. (Current Protein and Peptide Science, 2002)
The large, multifunctional proteins Factors V and VIII are cofactors in the coagulation cascade and possess a similar domain structure, A1-A2-B-A3-C1-C2. The C domains are related to the discoidin protein family, while the A domains are homologous to the copper-binding protein ceruloplasmin. After proteolytic activation, Factors V and VIII behave as peripheral membrane proteins, binding to negatively charged membranes containing phosphatidylserine, primarily via specific sites on their C2 domains. This type of membrane surface is exposed at sites of tissue damage, where platelets have become activated. The cofactors then accelerate sequential proteolytic activations that occur at critical control points in the blood coagulation cascade via complex formation with specific serine proteinases. Here we compare recent structural and functional studies of the C2 domains of Factors V and VIII, and discuss their respective roles. The membrane-binding motifs consist of several exposed hydrophobic side chains surrounded by a ring of basic residues, and the C2 domains appear poised to insert their hydrophobic “feet” into the membrane interior as basic residues interact favorably with phosphatidylserine head groups. In line with their physiological roles, the membrane-binding surfaces of the C2 domains display a good deal of mobility. We then extend our analysis to other members of the discoidin protein family, which perform diverse physiological functions involving signaling pathways at cell surfaces. Finally, structural similarities between discoidin proteins and the topologically distinct but functionally related membrane-binding “classic C2 domains”, including signal-transduction proteins such as Protein Kinase C and phospholipases, are noted.
Keywords: fva